Detection of a Magnetic Discontinuity in the Upper Solar Chromosphere Associated with a Coronal Loop Brightening Observed by CLASP2.1 - Donguk Song; Ryohko Ishikawa; David E. McKenzie; Javier Trujillo Bueno; Frédéric Auchère; Ryouhei Kano; Amy Winebarger; Takenori J. Okamoto; Laurel A. Rachmeler; Ken Kobayashi; Genevieve D. Vigil; Adam R. Kobelski; et al. (The Astrophysical Journal)
We report the first detection of a magnetic discontinuity in the upper solar chromosphere associated with a coronal loop brightening. Our findings are based on novel observations obtained by the Chromospheric LAyer SpectroPolarimeter (CLASP2.1) suborbital space experiment. During its short 6 minute flight, CLASP2.1 successfully obtained spectropolarimetric data across the Mg ii h and k lines, which allowed us to map the longitudinal magnetic field at multiple heights in the chromosphere of a solar active region. During our observation, we found a coronal loop brightening that was intermittently and recurrently heated. The temperature of the brightening plasma is above 2.5 MK, which is higher than the ambient temperature, and no corresponding brightening is detected in the images of the photosphere and lower chromosphere. The notable finding of our study is that the coronal loop brightening of interest is observed across a region where the magnetic field polarity changes abruptly in the upper chromosphere. Our results provide observational evidence that the heating mechanism of the coronal loop brightening is consistent with magnetic reconnection in the upper solar chromosphere.